Pengaruh Media Alat Peraga Papan Angka dan Model Pembelajaran Interaktif terhadap Hasil Belajar Peserta Didik Madrasah Ibtidaiyah - Didit Darmawan; Nila Talita Haditiyah; Denis Nurista Sari (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Madrasah Ibtidaiyah students often have difficulty understanding abstract concepts, requiring more concrete, interactive learning strategies that are appropriate for their cognitive development stage. This study examines the effect of using number boards combined with interactive learning models on student learning success, with the intention of offering a scientific foundation for educators in designing effective and innovative learning strategies. This investigation was carried out qualitatively through a literature review, analyzing relevant journals, articles, and previous studies. The Content analysis methods were used to examine the data, including reviewing, summarizing, comparing, and synthesizing previous research conclusions. The findings show that the use of number board media is proven to be effective in facilitating students' concrete understanding, increasing learning motivation, and creating a conducive and enjoyable learning environment. Meanwhile, the interactive learning model actively involves students through discussions, educational games, and group projects, thereby significantly improving understanding and learning outcomes. Thus, the combination of number board media and interactive learning models contributes positively to improving conceptual understanding, motivation, and student engagement, and should be optimized in Madrasah Ibtidaiyah learning to achieve better quality education.